Pertumbuhan Stek Batang Jarak Pagar (Jatropha curcas L.) dengan Perendaman Larutan Bawang Merah (Allium cepa L.) dan IBA (Indol Butyric Acid) - Mukarlina, Elly Siskawati, Riza Linda, (Universitas Tanjungpura, 2013)
Jatropha (Jatropha curcas L.) need to be propagated since this plant has many benefits, it can be applied to produce fuel, biodiesel and traditional medicine. The cultivation of this plant can be utilized by stem cuttings, however the process can be failed if the root was not formed. The use of Indole Butyric Acid (IBA) and onion extract which contain natural and synthetic growth regulators are needed to stimulate the growth of cutting roots. The purpose of this study was to investigate the effects of onion extracts and Indol Butyric Acid (IBA) for the growth of stem cuttings of jatropha. The study was conducted in a greenhouse at the Department of Biology, Faculty of Mathematics and Natural Sciences in University of Tanjungpura from October 2012 to January 2013. This study employed a randomized factorial design of 2 factors. The first factor was onion extracts and the second one was IBA. The concentrations in onion extracts were 0% , 40%, 60%, 80%, 100% and IBA were 0 ppm, 10 ppm, 20 ppm, 30 ppm, 40 ppm. Each treatment was repeated 3 times as a result there were 75 experimental units. The treatment with 100% of onion extracts produced the highest number of leaves (10.46 strands), air dried basis of shoots (44.91 g) and dry basis of shoots (7.39 g), while the effect of treatment with IBA produced the best number of roots (16.93 strands), air dried basis of roots (1.23 g) and dry basis of roots (0.51 g)